An Empirical Study on Initial Listing Performance of IPOs in India - Archana, H. N.; Srilaskhmi, D. (Indian Journal of Research in Capital Markets, 2019)
In this paper, we analyzed the initial listing performance of initial public offerings (IPOs) by computing the raw return (RR) and the market adjusted excess return (MAER). The study also identified and analyzed the factors that had an influence on the performance of IPOs. We used a sample of 239 IPOs offered during the period from 2016–2018 and examined the performance by employing factors such as offer price, issue size, and method of pricing. The analysis indicated that the offer price had a positive relationship towards the initial listing performance of IPOs ; whereas the issue size, market return, and listing delay showed a negative relationship towards the performance of IPOs. Apart from this, the study also highlighted that underpricing existed in Indian markets during the study period and the level of underpricing was high in fixed price method of issuing IPOs in comparison to book building method of issuing IPOs. It was also found that there was a significant relationship between initial listing performance of IPOs with varying offer price, varying issue size, method of pricing, and different sectors.